Self-assembled of nanolayered 2-acryamido-2-methylpropane sulfonate in the Zn/Al layered double hydroxide lamella - Hussein, M.Z.; Seng, H.K. (Kluwer Academic Publishers, 2001)
A report on the formation of a nanolayered organic of 2-acryamido-2-methylpropane sulfonate (AMPS) into the Zn-Al layered double hydroxide (LDH) inorganic lamella for the formation of new organic-inorganic hybrid nanocomposite was presented. The spontaneous self-assembly method was used for the synthesis of Zn-Al-LDH-AMPS nanolayered composite. The nanolayered composite was characterized using X-ray diffraction (XRD) and Fourier transform infrared radiation (FTIR) spectroscopy. An expansion of the interlamellar of the inorganic host was shown to accomodate the AMPS anions for the formation of Zn-Al-LDH-AMPS nanolayered hybrid structure.